Importin 7 and Importin α/Importin β Are Nuclear Import Receptors for the Glucocorticoid Receptor - Freedman, Neal D. (The American Society for Cell Biology, 2004)
The vertebrate glucocorticoid receptor (GR) is cytoplasmic without hormone and localizes to the nucleus after hormone binding. GR has two nuclear localization signals (NLS): NL1 is similar in sequence to the SV40 NLS; NL2 is poorly defined, residing in the ligand-binding domain. We found that GR displayed similar hormone-regulated compartmentalization in Saccharomyces cerevisiae and required the Sxm1 nuclear import receptor for NL2-mediated import. Two metazoan homologues of Sxm1, importin 7 and importin 8, bound both NL1 and NL2, whereas importin α selectively bound NL1. In an in vitro nuclear import assay, both importin 7 and the importin α-importin β heterodimer could import a GR NL1 fragment. Under these conditions, full-length GR localized to nuclei in the presence but not absence of an unidentified component in cell extracts. Interestingly, importin 7, importin 8, and importin α bound GR even in the absence of hormone; thus, hormonal control of localization is exerted at a step downstream of import receptor binding.